1998
DOI: 10.1071/ea97076
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of trifluralin in three Victorian soils —long-term field trials

Abstract: Summary. The persistence of trifluralin was investigated at 3 sites in southern Australia over 8 years. Persistence varied from year-to-year, with the highest persistence being recorded at all sites in the dry year of 1984. Trifluralin persistence (expressed as a percentage of the initial measured concentration) 1 year after application was lowest at Rutherglen (7–22%), followed by Dooen (7–26%) and Walpeup (13–120%). Trifluralin degradation at Walpeup in 1984 was negligible. The resultant high residue concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…However, there was consistency in the standard curves, with 50% inhibition of oat root growth occurring between 0.13 and 0.23 g trifluralin g Ϫ1 soil. This is similar to a previous study from Australia, where 50% inhibition of root growth was reported around 0.1 g trifluralin g Ϫ1 soil (Johnstone et al 1998).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, there was consistency in the standard curves, with 50% inhibition of oat root growth occurring between 0.13 and 0.23 g trifluralin g Ϫ1 soil. This is similar to a previous study from Australia, where 50% inhibition of root growth was reported around 0.1 g trifluralin g Ϫ1 soil (Johnstone et al 1998).…”
Section: Resultssupporting
confidence: 92%
“…In any case, weed control by trifluralin is not based on the total amount present but on its bioavailability. Therefore, a bioassay will provide information about the bioavailability of trifluralin (Johnstone et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…While the resistance trait is recessive, it may still be possible to select for resistance to trifluralin, so long as there is a rate of herbicide where there is greater survival of the heterozygote compared with the homozygous susceptible individuals. Trifluralin activity in the soil decays over a long period of time in Australian farming systems (Johnstone et al 1998). While heterozygous resistant individuals may be killed by the full dose of the herbicide, later-germinating weeds will be exposed to a lower dose, and differential survival may occur.…”
Section: Resultsmentioning
confidence: 99%
“…Rouchaud et al [27,28] have reported that the field dissipation of flufenacet accelerated with the higher temperatures in spring and summer due to increased soil microbial activities. Similarly, Johnstone et al [38] have found a relationship between the persistence of the herbicide trifluralin and weather conditions (total precipitation and maximum average temperatures) at 60 days after its repeated application in experimental plots.…”
Section: Relationship Between Dissipation Parameters and Weather Conditionsmentioning
confidence: 74%